1999
DOI: 10.1590/s0104-42301999000200017
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento da epistaxe

Abstract: Epistaxe é definida como o sangramento proveniente da mucosa nasal 1 . Calcula-se que 60% da população adulta já tenham apresentado ao menos um episódio de epistaxe 2 , na maioria das vezes auto-limitado e sem maiores conseqüências. Estima-se que apenas 6% dos casos de epistaxe necessitem de intervenção médica para contenção do sangramento 2 e a taxa de mortalidade por epistaxe maciça seja de menos de 0,01% 3 .No Pronto Socorro da Divisão de Clínica Otorrinolaringológica do Hospital das Clínicas da Faculdade d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
(43 reference statements)
0
7
0
5
Order By: Relevance
“…There are many nasal packs available, and the most commonly used are those by rayon or gauze. Other alternatives are the nasal packs created with glove fingers filled with gauze, regular household sponge inside a condom and Merocel packing 4,14 . When bleeding is posterior or when anterior nasal packing is not enough, there is a need for posterior nasal packing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are many nasal packs available, and the most commonly used are those by rayon or gauze. Other alternatives are the nasal packs created with glove fingers filled with gauze, regular household sponge inside a condom and Merocel packing 4,14 . When bleeding is posterior or when anterior nasal packing is not enough, there is a need for posterior nasal packing.…”
Section: Discussionmentioning
confidence: 99%
“…Epistaxis has a bimodal distribution in relation to age, with the first incidence peak during childhood and the next around 50 years and on 3,[13][14] . We believe our study has shown only one peak involving elderly patients, because of the hospital stay factor which results from more severe epistaxis, usually due to systemic diseases -more prevalent in older individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A epistaxe é classificada em anterior ou posterior, dependendo da origem do sangramento. Mais de 90% dos casos de epistaxe decorrem de sangramento na região anterior (BALBANI et al, 1999). O tratamento da epistaxe pode ser realizado de acordo com a gravidade, sendo possível utilizar as seguinte técnicas: rinoscopia anterior com cauterização química ou elétrica, tamponamento nasal anterior, eletrocoagulação guiada por endoscópio nasal, tamponamento nasal posterior ou tratamento cirúrgico (embolização ou ligadura arterial) (STRONG et al, 1995).…”
Section: Complicações Agudasunclassified